Redesigning a food bank supply chain network, Part II: Computational study - C. L. Martins; Teresa Melo; Margarida Vaz Pato (Hochschule für Technik und Wirtschaft des Saarlandes, Fakultät für Wirtschaftswissenschaften, 2017)
In Martins et al. (2016), we proposed a novel mixed-integer linear programming model to redesign a multi-echelon food bank supply chain network over a multi-period planning horizon. The three dimensions of sustainability, i.e. economic, environmental and social goals, were addressed by considering three conflicting objective functions in the model. In the present paper, which we refer to as Part II, we refine the mathematical formulation and present a computational study conducted on a set of test instances that reflect the characteristics of the food bank network managed by the Portuguese Federation of Food Banks in the south of Portugal. The trade-offs that occur under the three conflicting objectives are evaluated for a subset of non-dominated solutions obtained with lexicographic ordering. The insights drawn from several comparative analyses also contribute to a better understanding of the impacts of food collection and distribution.
Keywords: 650; food rescue and delivery; sustainability; supply chain network design; tri-objective problem; social impact; economic and environmental performance